2019
DOI: 10.3389/fpsyg.2019.00993
|View full text |Cite
|
Sign up to set email alerts
|

How Can Transcranial Magnetic Stimulation Be Used to Modulate Episodic Memory?: A Systematic Review and Meta-Analysis

Abstract: A systematic review and meta-analysis were conducted to synthesize the existing literature on how transcranial magnetic stimulation (TMS) has been used to modulate episodic memory. Given the numerous parameters of TMS protocols and experimental design characteristics that can be manipulated, a mechanistic understanding of how changes in the combination of parameters (e.g., frequency, timing, intensity, targeted brain region, memory task) modulate episodic memory is needed. To address this, we reviewed 59 studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 129 publications
(138 reference statements)
3
30
0
Order By: Relevance
“…In addition, the present results showed that 10 Hz rTMS stimulus is an effective parameter to enhance episodic memory. A meta-analysis indicated that off-line 20, 10, and 5 Hz rTMS were all effective to enhance episodic memory (Yeh and Rose, 2019). The present study further supported the high-frequency rTMS could promote source memory.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In addition, the present results showed that 10 Hz rTMS stimulus is an effective parameter to enhance episodic memory. A meta-analysis indicated that off-line 20, 10, and 5 Hz rTMS were all effective to enhance episodic memory (Yeh and Rose, 2019). The present study further supported the high-frequency rTMS could promote source memory.…”
Section: Discussionsupporting
confidence: 80%
“…The reason for the contradictory results might be that some studies have used single-session stimulation while others have used multi-session stimulation. Yeh and Rose (2019) reviewed all the rTMS studies on episodic memory, and they proposed that the implementation of high-frequency multi-session off-line rTMS could promote episodic memory in MCI and AD patients. Only a few studies have implemented multi-session off-line stimulation in healthy older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that the relationship between the intensity of cTBS stimulation and degree cortical suppression is complex and possibly non-linear, at least in some participants, casting doubt on the assumption that the behavioral effects of such stimulation should correlate positively with stimulation intensity (Sasaki et al, 2018). Further work is needed to establish the stimulation parameters that have the greatest likelihood of impacting episodic memory processes (Yeh & Rose, 2019;Widhalm & Rose, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear if our results would differ had we used a different TMS protocol, such as 1Hz rTMS. Of relevance to this point, a recent meta-analysis of TMS effects on episodic memory found that offline 1 Hz rTMS led to larger enhancing effects on episodic memory compared to other stimulation protocols, including iTBS (Yeh & Rose, 2019). Second, we only examined the effects of mPFC stimulation during memory encoding.…”
Section: Discussionmentioning
confidence: 99%
“…For example, as described above, Bovy and colleagues found a causal role of the mPFC in gist-based false memories implementing cTBS while our iTBS protocol revealed a causal role of the mPFC in emotional memory (collapsed across specific and gist-based memories). Of relevance to this point, a recent meta-analysis of TMS effects on episodic memory found that offline 1 Hz rTMS led to larger enhancing effects on episodic memory compared to other stimulation protocols, including iTBS (Yeh & Rose, 2019). Second, we only examined the effects of mPFC stimulation during memory encoding.…”
Section: Discussionmentioning
confidence: 99%